Invasive species’ environmental impacts are more severe in the Global South - Sven Bacher; Petr Pyšek; Hanno Seebens (Science, 2026)
Invasive alien species (IAS) are a major threat to biodiversity, yet their impact distribution remains poorly understood. Global biodiversity assessments suggest the highest impacts in wealthy countries of the Global North, but this is only inferred from IAS numbers, reflecting research bias. Using a new global database of standardized impact measures, we calculated average impact severity per country and found that it is higher in the Global South despite more than twice as many reports in the Global North. Weak governance and limited management capacity are the main drivers of high impact severity. Emerging economies with rapid economic growth but poor governance are particularly vulnerable. Failure to recognize the Global South as facing the highest IAS impacts diverts attention away from the most threatened regions.